Development of a low cost planar interdigital ammonia sensor for water quality sensing application – prototype / Norfarah Amira Jalal … [et al.] - Jalal, Norfarah Amira; Othman, Nor Azlan; Damanhuri, Nor Salwa; Ibrahim, Intan Rahayu; Abd Rahman, Mohamad Faizal; Ahmad, Anita (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Contaminated water does not only affect human beings, but the life of aquatic species also relies on clean water. Critical parameters such as dissolved oxygen (DO), the potential of hydrogen (pH), ammonia, nitrate and also temperature must be observed. Ammonia is toxic to fish and can be damaging to any fish production system. This paper presents three types of planar interdigital sensors that have been fabricated and developed for the aim of the aquaculture monitoring process. The objectives of this study are to develop and to characterize a sensor suitable for ammonia detection for aquaculture application; to evaluate the effectiveness of the sensor to detect the ammonia level in the water and also to develop a low cost ammonia sensor. There are several experiments conducted on these planar interdigital sensors to recognize which sensor produces a better sensitivity. These planar interdigital sensors are designed with the same number of positive electrodes but different numbers of negative electrodes. The experiment was carried out by using Impedance Analyzer IM3570 to obtain the data and NI myRIO-1900 was used to monitor the sensor application. Wheatstone bridge was used as signal conditioning to interface between the sensor and NI myRIO-1900. Graphical User Interface (GUI), programmed using LabVIEW was developed to interface between the hardware and the software parts. Results show that Sensor 1 has the best sensitivity compared to other sensors.